PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL INQUIRY TRAINING TERHADAP PEMAHAMAN KONSEP SISWA PADA MATERI GETARAN HARMONIS - Amelia, Isra; Azhar, Azhar; Irianti, Mitri (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2024)
This study aims to develop learning tools using the Inquiry Training model on Harmonic Vibration material. The learning tools developed are RPP, LKPD, and Concept Understanding Tests. The research method used is Research and development (R&D) to produce products and test the effectiveness of these products, in this case in the form of learning tools. Research design uses the 4D model, namely Define, Design, Development and Dissemination. The data collection technique was validated by a validator consisting of three people, namely, two supervising lecturers and one discussing lecturer. Based on the results of the study, it was obtained that the average validity-2 Learning Implementation Plans (RPP), Student Worksheets (LKPD), and concept understanding tests were 3.43 very high categories with validity criteria, namely valid. The results of the validity-2 RPP were 3.42 very high categories with validity criteria namely valid, the results of the validity-2 LKPD were 3.52 very high categories with validity criteria namely valid, and the results of the validity-2 concept understanding test were 3.36 very categories high with the criteria of validity that is valid. Based on the results of the data analysis obtained from the research conducted, it can be concluded that the development of learning tools oriented to the Inquiry Training learning model on SMA harmonic vibration material was declared valid by the validator with the results obtained in validation-2 being in the very high category and can be used as material teach in the learning process in schools.